Efficiency analysis of plantation companies in Malaysia: a data development analysis application / Mohd Nor Fikri Md Razali - Md Razali, Mohd Nor Fikri (Faculty of Plantation and Agrotechnology, 2018)
This paper presents a research study on the efficiency performance of the oil palm companies in Malaysia. A total of 20 performance companies from oil palm plantation sector listed in Bursa Malaysia were used the efficiency strength and return to scale analysis. The input oriented Data Envelopment Analysis models were employed in the analyses. Data were obtained from the annual financial statement of each companies for the year 2016. The overall result shows significant correlations among the variables. The DEA scores indicate that only 6 and 30% of the companies are operating on the best-practice frontier under the assumptions of return to scale (CRS). The rest will have difficulty in making themselves efficient in short term. An inefficient companies can be made more efficient by projection onto the frontier. Other than that, peers are efficient units that could acts as models for inefficient units to improve performance. A linear combination of these peers acts as a composite efficient DMU which identifies a corresponding efficient position on the frontier for the inefficient unit under evaluation.